Absence of Rybp Compromises Neural Differentiation of Embryonic Stem Cells - Gergo Kovacs; Viktoria Szabo; Melinda K. Pirity (Stem Cells International)
Rybp (Ring1 and Yy1 Binding Protein) is a transcriptional regulator and member of the noncanonical polycomb repressive complex 1 with essential role in early embryonic development. We have previously described that alteration of Rybp dosage in mouse models induced striking neural tube defects (NTDs), exencephaly, and disorganized neurocortex. In this study we further investigated the role of Rybp in neural differentiation by utilising wild type (rybp+/+) and rybp null mutant (rybp-/-) embryonic stem cells (ESCs) and tried to uncover underlying molecular events that are responsible for the observed phenotypic changes. We found that rybp null mutant ESCs formed less matured neurons, astrocytes, and oligodendrocytes from existing progenitors than wild type cells. Furthermore, lack of rybp coincided with altered gene expression of key neural markers including Pax6 and Plagl1 pinpointing a possible transcriptional circuit among these genes.